2008
DOI: 10.1007/s00468-007-0198-z
|View full text |Cite
|
Sign up to set email alerts
|

Stem CAM in arborescent succulents

Abstract: Stem CAM with a peripheral chlorenchyma in stem succulents growing up to arborescent sizes and life forms appears to be a unique evolution as it requires delayed and reduced bark formation and stem stomata. However, stem succulence as a convergent morphotype and with it the stem CAM physiotype evolved polyphyletically in many divergent taxa of the dicotyledonous angiosperms. Controlling water budgets is the main ecophysiological benefit of stem succulence and CAM, where the cooperation of a peripheral photosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 83 publications
2
11
0
Order By: Relevance
“…This could contribute to explaining the positive association observed between external nutrient concentration and water capacitance in stem tissues ( Figure 5). In fact, in other plant species, a close correlation was previously observed between osmotic pressure increases (or decreases in osmotic potential) and succulence parameters (Lüttge, 2008).It has been suggested that J. curcas has the ability to combine C 3 /CAM photosynthesis in succulent stems, while leaves are capable of altering their water use efficiency, changing their C 3 metabolism for CAM (Jongschaap et al, 2009). In Euphorbia tirucalli, a drought tolerant species with potential as a biofuel source, photosynthetic pathways include C 3 metabolism in non-succulent leaves and CAM in succulent stems (Hastilestari et al, 2013).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…This could contribute to explaining the positive association observed between external nutrient concentration and water capacitance in stem tissues ( Figure 5). In fact, in other plant species, a close correlation was previously observed between osmotic pressure increases (or decreases in osmotic potential) and succulence parameters (Lüttge, 2008).It has been suggested that J. curcas has the ability to combine C 3 /CAM photosynthesis in succulent stems, while leaves are capable of altering their water use efficiency, changing their C 3 metabolism for CAM (Jongschaap et al, 2009). In Euphorbia tirucalli, a drought tolerant species with potential as a biofuel source, photosynthetic pathways include C 3 metabolism in non-succulent leaves and CAM in succulent stems (Hastilestari et al, 2013).…”
Section: Resultssupporting
confidence: 66%
“…These succulent stems are differentiated in an outer green photosynthetically active chorenchyma and an internal water storing hydrenchyma (Lüttge, 2008). Cell walls of water storage tissues have a lower modulus of elasticity than those of the chlorenchyma, so that they can absorb and release more water with small changes in turgor potential (Lüttge, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This CAM physiotype has previously been reported in some stem succulent Euphorbia species (Pearcy & Troughton 1975;Willert et al 1985;Martin et al 1990;Van Damme 1991;Mies et al 1996;Elhaak et al 1997;Winter et al 2005;Ameh 2006;Feakins and Sessions 2010). Nocturnal CO 2 uptake and daytime stomatal closure characteristic of CAM imply avoidance of gas exchange when environmental conditions favor transpirational water loss and hence enhanced plant water economy (Walker & Leegood 1996;Winter & Smith 1996;Borland et al 2000;Sayed 2001b;Luttge 2004;Lu¨ttge 2008;Herrera 2009). However, during the long dry season, E. fractiflexa exhibited very low values of stomatal conductance during both day and night (Figure 1) and markedly dampened diurnal oscillation of cell sap titratable acidity (Figure 2).…”
Section: Discussionmentioning
confidence: 98%